THE EVOLVING ADAPTIVE NEURAL NETWORK FOR DATA PROCESSING WITH MISSING OBSERVATIONS - Shafronenko, A.; Pliss, I.; Bodyanskiy, Ye. (Radio Electronics, Computer Science, Control, 2013)
The problem of computational intelligence systems synthesis in on-line mode, capable for processing stochastic signals with missing observations in the data is considered. An adaptive approach based on using of orthogonal polynomials is developed.